Acid-free preparation and characterization of kelp (Laminaria japonica) nanocelluloses and their application in Pickering emulsions. (15th May 2020) - Wu, Jiulin; Zhu, Wenjin; Shi, Xiaodan; Li, Qingxiang; Huang, Chenguang; Tian, Yongqi; Wang, Shaoyun
Highlights: Kelp CNFs and TEMPO-CNFs were prepared by an acid-free, low-energy method. TEMPO-CNFs showed smaller particle size and more uniform. TEMPO-CNFs Pickering emulsion presented better performances. The pH 3 was beneficial to improve the TEMPO-CNFs emulsion performances. TEMPO-CNFs could emulsify higher content of sunflower oil (50 %). Abstract: Cellulose nanofibers (CNFs) from kelp were prepared by cellulase treatment with lengths greater than 3 μm. CNFs were further oxidized by TEMPO-oxidized system, and the lengths of the oxidized CNFs (TEMPO-CNFs) were 0.6−1 μm. AFM and TEM images showed that intertwined CNFs fibers were divided into individual nanofibrils. The crystallinity of TEMPO-CNFs increased to 66.5 %. TGA analysis indicated that TEMPO-CNFs were more sensitive to temperature than cellulose and CNFs. FT-IR spectra revealed no changes in the basic cellulose structures of CNFs and TEMPO-CNFs. In the sunflower oil/water (20/80, v/v) model emulsions, the oil droplet sizes were less than 20 μm in CNFs emulsions, which became smaller in TEMPO-CNFs emulsions. Delamination was found in CNFs emulsions after three days of storage. Addition of NaCl increased the volumes of TEMPO-CNFs emulsions but enlarged the oil droplets sizes. TEMPO-CNFs emulsions had the largest volume with smallest and most homogeneous oil droplets at pH 3. TEMPO-CNFs emulsions showed good stability after storage for 30 days. Further, TEMPO-CNFs could also emulsify 50 % (v/v) of sunflower oil. All these results indicated that TEMPO-CNFs can be used in preparing Pickering emulsions.